THEORETICAL FOUNDATIONS OF INNOVATION SYSTEMS IN SOCIAL AND ECONOMIC ENVIRONMENT OF REGIONS - Jurayeva Gavhar Toshboboyevna (American Journals Publishing, 2023)
This article discusses the stages of life-cycle of territorial innovation systems, classification of the territorial innovation systems, the factors of influencing innovation potential and structure of innovation potential of the territories.
Keywords: The Republic of the Uzbekistan, territory, innovation system, innovation system of the territory.